Effect of Xiaoxuming Decoction on Aβ and GFAP Protein Expressions in Hippocampus of APP/PS1 Mouse Model of Alzheimer's Disease and Its Behavior Analysis - Jingjie MAO; Yaping CHEN; Ruhui LIN; Zuanfang LI; Xiaoqin ZHU (康复学报)
Objective:To observe the effect of Xiaoxuming decoction (XXMD) on the expression of Aβ and GFAP protein in the hippocampus of APP/PS1 transgenic model mouse, and to explore its mechanism.Methods:APP/PS1 double transgenic mice were used to establish the Alzheimer's disease (AD) model, and the same month old littermates negative mice were chose as the control group. Transgenic mice were divided into the model group and the Xiao Xu Ming group by a random number table, the control group and the model group didn't receive medicine treatment. Xiao Xu Ming group received XXMD at a dose of 13 g/kg for 90 days. Morris water maze experiment was used to observe the learning and memory ability of mice, and immunohistochemical staining was used to observe the expression of Aβ and GFAP proteins in the hippocampus of three groups.Results:Compared with the model group, the time of arrival in the target area and search distance in the Xiao Xu Ming group were significantly shortened (P<0.05), and the times across platform were significantly increased (P<0.05). Immunohistochemical results showed that compared with wild group, both of Aβ protein deposition and GFAP positive cells were increased significantly in hippocampus of the transgenic group (P<0.01). Compared with the model group, the Aβ protein deposition and GFAP positive cells were decreased in the Xiao Xu Ming group (P<0.05).Conclusion:XXMD can improve the cognitive function of APP/PS1 transgenic mice, which may be associated with down-regulation of Aβ and GFAP expression in hippocampus.